Peran Modul Kebhinekaan Dari Kegiatan Kampus Merdeka Inbound 4 Universitas Mataram Dalam Rangka Peningkatan Pengetahuan Budaya Bangsa Indonesia: Peran Modul Kebhinekaan Dari Kegiatan Kampus Merdeka Inbound 4 Universitas Mataram Dalam Rangka Peningkatan Pengetahuan Budaya Bangsa Indonesia - Hasbi, Nurmi (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Diversity activities are diversity promotion activities held by recipient universities. Diversity activities are carried out in eight activities. This diversity aims to introduce the culture in recipient universities through visits and interactive discussions with resource persons. This diversity activity is carried out by 1 lecturer of the archipelago module, 1 liaison officer and 23 students participating in the archipelago module. The eight diversity activities include visits to the NTB state museum, Sade traditional village, Beleg Rinjani traditional village, Lingsar Temple, Jinapanjara Temple, Rembitan ancient mosque, three Gili (Gili Air, Gili Meno and Gili Trawangan) and the coast of Mataram City. This diversity activity is carried out for 4 months which is carried out every week. Student participation in this activity shows high enthusiasm. This activity is expected to not only increase cultural understanding, but also strengthen the sense of solidarity between students and the local community.